„Na ulicy czeka na mnie deszcz” – analiza motywu deszczu w twórczości Wiktora Coja - Paulus, Jędrzej Melchior (Studia Rossica Posnaniensia, 2012)
Viktor Tsoi and his band KINO were some of the most well-known musicians of the late 1980s in the former USSR. Their influence on Russian rock-culture has been quite large and their output started being analyzed a few years ago. One of the main themes in Tsoi’s poems and songs is rain. This work is an attempt to interpret this motif in some of Tsoi’s most important songs. The author, after his analysis, concludes that rain is always combined with some strong negative feelings, such as sadness or anger.